The Analysis of Workload and the Effectiveness of Doctor-Nurse Collaboration in Emergency Patient Management at Primary Health Centers: Analysis of Workload and the Effectiveness of Doctor-Nurse Collaboration in Emergency Patient Management at Primary Health Centers - Harefa, Karnirius (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Abstract The collaboration between doctors and nurses plays a crucial role in managing emergency patients at community health centers (Puskesmas). However, a high workload can hinder the effectiveness of teamwork and impact service quality. This study aims to analyze the relationship between workload and the efficacy of doctor-nurse collaboration in Puskesmas. This cross-sectional study involved 120 respondents (50 doctors, and 70 nurses) selected through purposive sampling. Data were collected using the WISN questionnaire (workload) and CPAT questionnaire (collaboration), and then analyzed using chi-square tests, t-tests, and logistic regression. The results showed that the average workload score for doctors was 75.3 ± 12.5 and for nurses was 82.1 ± 10.8, with a collaboration effectiveness score of 68.4 ± 9.7. A high workload was correlated with lower collaboration effectiveness (p = 0.012; OR = 2.45) and was identified as the main factor reducing collaboration effectiveness (AOR = 3.12; p < 0.001). Another influencing factor was work experience (AOR = 2.08; p = 0.045). Excessive workload poses risks of fatigue, stress, and communication breakdowns within the medical team, ultimately hindering coordination in patient management. The study concludes that a high workload negatively affects the effectiveness of doctor-nurse collaboration in handling emergency patients. To improve service quality in Puskesmas, additional healthcare personnel, optimization of the triage system, and training in communication and teamwork are necessary.